Dynamic web for land registration towards the adoption of land administration domain model in Nigeria - Babalola Sunday Oyetayo, 1968-, author; Alias Abdul Rahman, supervisor; Tan Liat Choon, supervisor; Fakulti Geoinformasi Dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Geoinformatik)) - Universiti Teknologi Malaysia, 2018